The Influence of Brand Awareness, Price, and Product Quality on Purchase Decisions with Social Media Marketing as a Moderator: A Case Study at D’Coffee Cup Merr Surabaya - Nurhadi; Dina Irawan (Jurnal Manajemen, 2026)
The rapid growth of the coffee industry in Indonesia has intensified competition, making it crucial for businesses to understand the factors influencing consumer purchase decisions. This study aims to analyze the influence of Brand Awareness, Price, Product Quality, and Social Media Marketing on Purchase Decisions, with Social Media Marketing examined as a moderating variable. A quantitative approach was employed by distributing questionnaires to 121 respondents, and the data were analyzed using validity and reliability tests, the Durbin–Watson autocorrelation test, and multiple linear regression with moderation analysis. The validity test results showed all items were valid (r count > r table, significance < 0.05) and reliable (Cronbach’s Alpha > 0.6), while the Durbin–Watson value of 1.896 indicated no autocorrelation. The results reveal that Brand Awareness, Price, and Product Quality simultaneously have a significant effect on Purchase Decisions. Partially, Brand Awareness and Price exert a positive and significant influence, whereas Product Quality shows a positive but insignificant effect. Social media Marketing significantly moderates the relationship between Brand Awareness and Purchase Decisions, as well as between Product Quality and Purchase Decisions, but not between Price and Purchase Decisions. These findings underscore the importance of digital marketing in strengthening brand recognition and perceived product quality in driving consumer behavior.